Imposto de renda e distribuiç\~ao de renda no Brasil - Rodrigo Cardoso Fernandes; Bernardo P. Campolina Diniz; Fernando Gaiger da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The Brazilian tax system places undue emphasis on indirect taxes - which comprise over 51% of its gross tax burden. The country's insistence on taxes on goods and services (indirect taxes) - to the detriment of taxes on income and property (direct taxes) - undermines the real application of the principle of contributive capacity, resulting in a regressive system whereby families with less income proportionally finance a larger share of the State. In the study, we analyze this disturbing national quirk in light of the evolution of the tax systems of certain central countries and draw comparisons with their current legislation. In addition to being normatively biased, Brazilian tax legislation has several technical limitations for the application of more efficient and equitable taxation on property and income. We undertake an exercise applying the Pareto interpolation method, using the 2008-2009 Household Budget Survey and the Large Numbers of Individual Income Tax Declarations (DIRPF), to estimate the level of inequality resulting from changes to personal income tax legislation. The key variable in the analysis is the reinstatement of taxation on profits and dividends, which are currently tax exempt. To that end, we have developed two simulations: one taxing profits and dividends at a 15% flat rate, and the other at a progressive rate varying between 15.0% and 27.5%. The results indicate a small improvement in income distribution, which is modest given the high level of income concentration in the country. On the other hand, there is a significant increase in revenue, between R 22 billion and R 39 billion, depending on the model for the taxation of profits and dividends. Finally, we performed a counterfactual exercise, whereby the additional revenue generated by the adoption of taxes on profits and dividends was used to fund an increase in public expenditure in several areas. The result was an improvement in income distribution.
Keywords: D31; D63; H53; H2; 330; taxes and inequality; progressivity; income concentration; Pareto's interpolation